Association of Serum Myeloperoxidase Level with Risk of Coronary Artery Disease in Patients with Type 2 Diabetes - Huda S. Abdulghani1 , Sura A. Abdulsattar2 , Essam N. Salman3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: This study aimed to investigate if the change of serum myeloperoxidase (MPO) level would be associated with the incidence of coronary artery disease (CAD) in the type 2 diabetic patients. Method: Eighty-eight (88) Iraqi subjects were grouped into three categories:(29) Type 2 diabetes mellitus patients and (29) diabetic patients with CAD compared with (30) healthy person. Serum Myeloperoxidase was performed by using ELISA kit. Fasting blood sugar and lipid profile were done by Roche/Hitachi cobas c 311device. Atherogenic index (AI) and Coronary risk index (CRI) were estimated. Results: The results of myeloperoxidase (ng/mL) indicate highly significant increase (p<0.01) in the sera of type 2 diabetic (54.18±22.62) and diabetic with CAD (70.79±35.90) patients groups in comparison to that level in control group (29.94±11.11). Meanwhile indicate highly significant differences between T2DM group and diabetic with CAD group. The results of FBS, HDL, triglyceride, VLDL, CRI and AI indicate a significant (p< 0.05) differences between all studied groups. While the results of Cholesterol and LDL indicate no significant (p?0.05) differences between control, T2DM and diabetic with CAD groups. Conclusion: Elevated level of MPO are association with the presence of Coronary Artery Disease in type 2 diabetic patients. These findings support a potential role of MPO as an inflammatory marker.